A Call for Preventive Medicine Attention for Indonesian Physicians - Laurentius Aswin Pramono (Acta Medica Indonesiana)
The year of 2020 teaches us to prevent is always better than to cure. It is an old phrase that is being used for decades, but it is never been implemented cordially by our society nowadays. Covid-19 is a good lesson that reminds us to carefully prevent the spread of coronavirus which is now a pandemic worldwide. People now wash their hands more often and clean, wear a mask everywhere – everytime, do physical distancing, do healthy lifestyle such as physical activity, healthy diet, and consume multivitamins. They obey the cough and sneeze etiquette. Prevention awareness is never been such popular like todays.